Antimicrobial Properties of Cocos nucifera: A Review - Ramaswamy, Lalitha; Rajendran, R.; Saraswathi, U.; Sughanya, R.; Geethadevi, C. (International Coconut Community Journal, 2015)
Coconut is known as the “wonder food” and is regarded as perfect diet because it contains almost all essential nutrients needed by the human body. The various products of coconut include tender coconut water, copra, coconut oil, raw kernel, coconut cake, coconut toddy, coconut shell and wood based products, coconut leaves, coir pith etc. Coconut is a unique source of various natural products for the development of medicines against various diseases and also for the development of industrial products. Almost all the parts of the palm have medicinal properties such as antibacterial, antifungal, antiviral, antiparasitic, antidermatophytic, antioxidant, hypoglycemic, hepatoprotective and immunostimulant property. The various medicinal properties of coconut and its products are summarized in this paper.